Internalisasi Nilai-Nilai Keagamaan Pada Pengasuh di Lembaga Kesejahteraan Sosial Anak ST. Khadijah Jakarta Selatan - Sahrul, Muhammad; Rahman, Irhamni; Ramdoni, Alfan (Universitas Muhammadiyah Sumatera Utara, 2024)
St Khadijah Children's Social Welfare Centre (LKSA) South Jakarta provides services and care to children from underprivileged families to support the family economy. As a non-formal institution under Muhammadiyah, this LKSA involves neglected children, such as orphans, school dropouts, and underprivileged children. This research adopts a qualitative approach with primary and secondary data collection from various documents and literature. The results show that St Khadijah's LKSA is active in embracing and meeting the needs of foster children, offering social services to meet children's needs and supporting the family economy. This LKSA integrates religious values through worship activities, memorising hadith, reciting the Qur'an, dhikr, reading tahlil, and surat yasin, as well as holding Islamic studies. Value internalisation involves value transformation, value transaction, and value internalisation. Value transformation explains and rationalises the values of worship, value transactions are conducted through interactive learning, and value transinternalisation involves verbal communication as well as the development of children's mental attitudes and personalities during prayers, briefings, and discussions.Keywords; internalisation, values, religion